Lego DC Shazam! Magic and monsters [videorecording (DVD)] (Warner Bros. Home Entertainment, 2020)
When the boy hero Shazam is offered to join the Justice League he is reluctant about it, but when his rivals the Monster Society put the League in peril he's the only one who can save them.